PEMBERHENTIAN SEMENTARA KEPALA DAERAH DAN / ATAU WAKIL KEPALA DAERAH KARENA MELAKUKAN TINDAK PIDANA (TINJAUAN YURIDIS ATAS PASAL 83 UNDANG-UNDANG NO. 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH) (Lex Jurnalica, 2017)
AbstrakThis paper discusses two issues related to the temporary dismissal of the regional head and / or the deputy head of the region for committing a crime under Article 83 of Law no. 23 Year 2014 on Regional Government. First Issue; What is the reason for the temporary dismissal of the regional head and / or deputy regional head under Article 83 of Law no. 23 Year 2014 on Regional Government. Second problem, when the regional head and / or deputy regional head are temporarily suspended from his / her position according to Article 83 of Law no. 23 Year 2014 on Regional Government. Editorial